The merger of Islamic banks in Indonesia: Do financial ratios and inflation matter? - Febriandika, Nur Rizqi; Fahira, Farah Fanda; Hakim, Faris Kurnia (Falah: Jurnal Ekonomi Syariah, 2026)
The study aims to investigate the effect of financial ratios and inflation on the stock price of Bank Syariah Indonesia using the Autoregressive Distributed Lag (ARDL) approach. This research was quantitative with variables studied include the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Net Operating Margin (NOM), Operating Costs to Operating Income (BOPO), Financing to Deposit Ratio (FDR), and Inflation. Data were observed from the BSI bank merger in February 2021 to August 2024 by using the Autoregressive Distributed Lag (ARDL) method. The results indicate that in the long term, all variables have no significant effect on stock prices. Meanwhile, in the short term, ROA had a significant positive effect on stock prices, NOM and FDR had a significant negative effect, while CAR, BOPO, and inflation had no significant effect on stock prices, indicating stock price dynamics. Thus, the findings of this study indicate that investors are more responsive to changes in the financial performance of Indonesian Islamic banks in the short term than in the long term. This research contributes theoretically by showing that market responses to firm fundamentals and economic conditions occur through gradual adjustment rather than instant reactions. Practically, the findings assist investors and policymakers in understanding key fundamental and macroeconomic determinants of stock prices for the stability of Islamic banking.